Mathematical Model of Free Convection Boundary Layer Flow on Solid Sphere with Viscous Dissipation and Thermal Radiation - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Abid, Hussanan; Norhafizah, Md Sarif; Nor Aida Zuraimi, Md Noar; Anuar, Ishak; Widodo, Basuki (IJCSAM, 2016)
—Present study considers the mathematical modeling of free convection boundary layer ﬂow and heat transfer on a solid sphere with viscous dissipation and thermal radiation effects. The transformed partial differential equations are solved numerically by using the Keller-box method. Numerical solutions are obtained for the reduced Nusselt number, the local skin friction coefﬁcient, the velocity and temperature proﬁles. The features of the ﬂow characteristics for various values of the Prandtl number, radiation parameter and Eckert number are discussed. It is worth mentioning that the results are obtained until x = 180◦. This is contrary to the previous report where the separation boundary layer ﬂow occurs after x = 120◦. The results in this paper is important for the researchers working in the area of boundary layer ﬂow and this can be used as reference and also as complement for comparison purposes in the future.